Evelyn ARIZPE, Teresa COLMER, Carmen Martínez-Roldán and contributors. Visual Journeys Through Wordless Narratives: An International Inquiry with Immigrant Children and The Arrival. London: BLOOMSBURY, 2014. 272p. ISBN-978-1-7809-3758-8 - Severson, Shawn (Linguarum Arena, 2014)
.